The Challenges of COVID-19 in Medical Education in Nepal - Vikash Paudel; Saraswoti Neupane (Nepal Journal of Dermatology, Venereology & Leprology)
The Coronavirus Disease-2019 (COVID-19) pandemic has caused an unparalleled disruption in all forms of scientific learning process including medical education. It has presented a challenge for scientists, educators, and students.Widespread interruptions to medical education, scientific discussions, conference, and seminars have also been seen at times of major conflicts and pandemics in the past as well, which resulted in major changes in medical curriculum.  This editorial discusses the medical education and how COVID-19 has affected medical education in Nepal. Besides, it also explores the potential implications of COVID-19 for the future of medical education.